The Catechumenate in late antique Africa (4th-6th centuries): Augustine of Hippo, his contemporaries and early reception - Pignot, Matthieu (Vigiliae Christianae, 2020)
Introduction -- Augustine the Catechumen: Patterns and Narrative -- The Practices and Status of catechumeni in Augustine's Community -- Catechumens Taking the Step: The Negotiation of Baptism in Augustine's Pastoral Care -- From catechumenus to fidelis: The Lenten Preparation for Baptism in Hippo -- Councils, Preaching and the Catechumenate in Fourth- and Fifth-Century Africa -- Epilogue